A scoping review on the impact of ambient temperature on human infertility - Seulkee Heo; Garam Byun; Yongsoo Choi; Yimeng Song; Mercedes Bravo; Tian Ma; Rory Stewart; Audrey Amezcua-Smith; Ji-Young Son; Leo Goldsmith; Kate Burrows; Hayon Michelle Choi; et al. (Environmental Research, 2026)

De-energization as maladaptation: Uneven residential exposure to wildfire Public Safety Power Shutoffs and compound heat - Kate Burrows; Kathryn McConnell; Nora Louise Schwaller; Chantel F. Pheiffer (Global Environmental Change, 2025)

Long-term PM2.5 exposure and mental health disparities: A prospective analysis of the All of Us Research Program - Kate Burrows; Jiajun Luo; Yuxuan Cai; Briseis Aschebrook-Kilfoy (Environmental Research, 2025)

Metrics of Urbanicity and Rurality in US-Based Epidemiologic Studies of Ambient Temperature and Health: A Scoping Review - Nicholaus P. Johnson; Alexandra Del Favero-Campbell; Amruta Nori-Sarma; Audrey Amezcua-Smith; Brandon Lewis; Chen Chen; Chengyi Lin; Damien Foo; Garam Byun; Hayon Michelle Choi; Honghyok Kim; Jesse D. Berman; et al. (Current Environmental Health Reports, 2025)

Is residential exposure to oil refineries a novel contextual risk factor for coronary heart disease? - Honghyok Kim; Natalia Festa; Kate Burrows; Dae Cheol Kim; Thomas M. Gill; Michelle L. Bell (Environmental Research, 2024)

Applying Mendelian randomization to appraise causality in relationships between nutrition and cancer - Kaitlin H. Wade; James Yarmolinsky; Edward Giovannucci; Sarah J. Lewis; Iona Y. Millwood; Marcus R. Munafò; Fleur Meddens; Kimberley Burrows; Joshua A. Bell; Neil M. Davies; Daniela Mariosa; Noora Kanerva; et al. (Cancer Causes & Control, 2022)
Dietary factors are assumed to play an important role in cancer risk, apparent in consensus recommendations for cancer prevention that promote nutritional changes. However, the evidence in this field has been generated predominantly through observational studies, which may result in biased effect estimates because of confounding, exposure misclassification, and reverse causality. With major geographical differences and rapid changes in cancer incidence over time, it is crucial to establish which of the observational associations reflect causality and to identify novel risk factors as these may be modified to prevent the onset of cancer and reduce its progression. Mendelian randomization (MR) uses the special properties of germline genetic variation to strengthen causal inference regarding potentially modifiable exposures and disease risk. MR can be implemented through instrumental variable (IV) analysis and, when robustly performed, is generally less prone to confounding, reverse causation and measurement error than conventional observational methods and has different sources of bias (discussed in detail below). It is increasingly used to facilitate causal inference in epidemiology and provides an opportunity to explore the effects of nutritional exposures on cancer incidence and progression in a cost-effective and timely manner. Here, we introduce the concept of MR and discuss its current application in understanding the impact of nutritional factors (e.g., any measure of diet and nutritional intake, circulating biomarkers, patterns, preference or behaviour) on cancer aetiology and, thus, opportunities for MR to contribute to the development of nutritional recommendations and policies for cancer prevention. We provide applied examples of MR studies examining the role of nutritional factors in cancer to illustrate how this method can be used to help prioritise or deprioritise the evaluation of specific nutritional factors as intervention targets in randomised controlled trials. We describe possible biases when using MR, and methodological developments aimed at investigating and potentially overcoming these biases when present. Lastly, we consider the use of MR in identifying causally relevant nutritional risk factors for various cancers in different regions across the world, given notable geographical differences in some cancers. We also discuss how MR results could be translated into further research and policy. We conclude that findings from MR studies, which corroborate those from other well-conducted studies with different and orthogonal biases, are poised to substantially improve our understanding of nutritional influences on cancer. For such corroboration, there is a requirement for an interdisciplinary and collaborative approach to investigate risk factors for cancer incidence and progression.

Simulating rewetting events in intermittent rivers and ephemeral streams: A global analysis of leached nutrients and organic matter - Oleksandra Shumilova; Dominik Zak; Thibault Datry; Daniel von Schiller; Roland Corti; Arnaud Foulquier; Biel Obrador; Klement Tockner; Daniel C. Allan; Florian Altermatt; María Isabel Arce; Shai Arnon; et al. (Global Change Biology, 2019)
Climate change and human pressures are changing the global distribution and the extent of intermittent rivers and ephemeral streams (IRES), which comprise half of the global river network area. IRES are characterized by periods of flow cessation, during which channel substrates accumulate and undergo physico‐chemical changes (preconditioning), and periods of flow resumption, when these substrates are rewetted and release pulses of dissolved nutrients and organic matter (OM). However, there are no estimates of the amounts and quality of leached substances, nor is there information on the underlying environmental constraints operating at the global scale. We experimentally simulated, under standard laboratory conditions, rewetting of leaves, riverbed sediments, and epilithic biofilms collected during the dry phase across 205 IRES from five major climate zones. We determined the amounts and qualitative characteristics of the leached nutrients and OM, and estimated their areal fluxes from riverbeds. In addition, we evaluated the variance in leachate characteristics in relation to selected environmental variables and substrate characteristics. We found that sediments, due to their large quantities within riverbeds, contribute most to the overall flux of dissolved substances during rewetting events (56%–98%), and that flux rates distinctly differ among climate zones. Dissolved organic carbon, phenolics, and nitrate contributed most to the areal fluxes. The largest amounts of leached substances were found in the continental climate zone, coinciding with the lowest potential bioavailability of the leached OM. The opposite pattern was found in the arid zone. Environmental variables expected to be modified under climate change (i.e. potential evapotranspiration, aridity, dry period duration, land use) were correlated with the amount of leached substances, with the strongest relationship found for sediments. These results show that the role of IRES should be accounted for in global biogeochemical cycles, especially because prevalence of IRES will increase due to increasing severity of drying events.

Mitochondrial DNA reveals multiple Northern Hemisphere introductions of Caprella mutica (Crustacea, Amphipoda) - GAIL V. ASHTON; MARK I. STEVENS; MARK C. HART; DAVID H. GREEN; MICHAEL T. BURROWS; ELIZABETH J. COOK; KATE J. WILLIS (Molecular Ecology, 2008)
Caprella mutica (Crustacea, Amphipoda) has been widely introduced to non‐native regions in the last 40 years. Its native habitat is sub‐boreal northeast Asia, but in the Northern Hemisphere, it is now found on both coasts of North America, and North Atlantic coastlines of Europe. Direct sequencing of mitochondrial DNA (cytochrome c oxidase subunit I gene) was used to compare genetic variation in native and non‐native populations of C. mutica . These data were used to investigate the invasion history of C. mutica and to test potential source populations in Japan. High diversity (31 haplotypes from 49 individuals), but no phylogeographical structure, was identified in four populations in the putative native range. In contrast, non‐native populations showed reduced genetic diversity (7 haplotypes from 249 individuals) and informative phylogeographical structure. Grouping of C. mutica populations into native, east Pacific, and Atlantic groups explained the most among‐region variation (59%). This indicates independent introduction pathways for C. mutica to the Pacific and Atlantic coasts of North America. Two dominant haplotypes were identified in eastern and western Atlantic coastal populations, indicating several dispersal routes within the Atlantic. The analysis indicated that several introductions from multiple sources were likely to be responsible for the observed global distribution of C. mutica , but the pathways were least well defined among the Atlantic populations. The four sampled populations of C. mutica in Japan could not be identified as the direct source of the non‐native populations examined in this study. The high diversity within the Japan populations indicates that the native range needs to be assessed at a far greater scale, both within and among populations, to accurately assess the source of the global spread of C. mutica .

Distribution of the introduced amphipod, Caprella mutica Schurin, 1935 (Amphipoda: Caprellida: Caprellidae) on the west coast of Scotland and a review of its global distribution - Gail V. Ashton; Kate J. Willis; Elizabeth J. Cook; Michael Burrows (Hydrobiologia, 2007)